Internalisasi Nilai Tawakal pada Santri di Pondok Pesantren Badrul Ulum Al-Islami Pacet–Kabupaten Bandung - Pupu Fakhrurrozi (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2018)
This research was conducted in Pondok Pesantren Badrul Ulum Al-Islami as salaf Islamic boarding school which was founded in 1918 and still exist until now. The method used in this research is descriptive method with qualitative approach and supported by literature study. The result obtained from this research are: The goal of internalization of tawakal value with zikr ya wakil is for clearing the soul (saffat asraruhu). Internalization process of tawakal value among others applied in activity of congregation of zikr, learning activity, and activity daily. The result of internalization of the value of tawakal is that the person will have a happy feeling. The obstacle are not yet thoroughly awareness of the internalization of tawakal value, the existence of takhassus student under the age of high scholl, and the lack of cohesiveness amongst students in order to help maximaze pondok pesantren’s program.